Techniques of Audiovisual Distraction to Reduce Pain during Venous Blood Sampling: A Case Study - Natalia Jayanti Mandasari; Leli Ngatikoh; Murniati (Genius Journal, 2022)
Objective: The purpose of this study was to determine whether there is an effect of audiovisual distraction therapy on reducing pain levels in pediatric patients when taking venous blood in cases of Dengue Hemorrhagic Fever. Method: The design used in this study is a descriptive study with a case study method for the provision of nursing care, namely from assessment, developing of nursing diagnoses, interventions, implementation and evaluation. The focus of the study was the effect of audiovisual distraction techniques on reducing pain scales in children who received invasive venous blood sampling. Result: The result is that after being given distraction therapy for 10  minutes for 3 days at the time of blood sampling, the respondent's pain level decreased from a scale of 8 on the first day to a scale of 2 on the third day. The audiovisual distraction therapy can be degrees pain level. Conclusion: This case study underscores the importance of the active involvement of nurses during invasive procedures that cause pain, one of which is taking venous blood in pediatric patients, so that pediatric patients are more cooperative.